2012
DOI: 10.1007/s10544-012-9665-4
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental characterization of a novel modular passive micromixer

Abstract: This paper reports a new low-cost passive microfluidic mixer design, based on a replication of identical mixing units composed of microchannels with variable curvature (clothoid) geometry. The micromixer presents a compact and modular architecture that can be easily fabricated using a simple and reliable fabrication process. The particular clothoid-based geometry enhances the mixing by inducing transversal secondary flows and recirculation effects. The role of the relevant fluid mechanics mechanisms promoting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…As the Reynolds number increases, the strength of secondary flows increases and mixing index becomes greater. Similar trends were reported by several researchers for Newtonian fluids [5,20,30] and by Afzal and Kim [1] for Carreau-Yasuda model of non-Newtonian fluids. In addition, by decreasing the power-law index and consequently increasing of apparent viscosity, the chaotic advection effect is weakened by viscous forces and as a result the degree of mixing decreases.…”
Section: The Mixing Performance Of Considered Micromixerssupporting
confidence: 90%
See 1 more Smart Citation
“…As the Reynolds number increases, the strength of secondary flows increases and mixing index becomes greater. Similar trends were reported by several researchers for Newtonian fluids [5,20,30] and by Afzal and Kim [1] for Carreau-Yasuda model of non-Newtonian fluids. In addition, by decreasing the power-law index and consequently increasing of apparent viscosity, the chaotic advection effect is weakened by viscous forces and as a result the degree of mixing decreases.…”
Section: The Mixing Performance Of Considered Micromixerssupporting
confidence: 90%
“…In addition, they reported that among the studied cases, the full three-stream (FTS)-CSC micromixer is more appropriate. Pennella et al [20] studied mixing efficiency of a novel configuration of split and recombination micromixer with curved segments, both experimentally and computationally. They investigated flows at Reynolds number between 10 and 110 and found that secondary flows and recirculation effect can be able to promote mixing performance.…”
Section: Introductionmentioning
confidence: 99%
“…The shearing channels are characterized by a constant height (50 μm) and a varying width (ranging from 15 to 120 μm) and have a total priming volume of about 1 μL The whole platform can be perfused with about 200 μL of platelets. The design of the mixing sub-unit was optimized by means of numerical modeling, in terms of channel length and number of repeating herringbone structures, as previously reported (78).…”
Section: Novel Microfluidic Platforms For Device-specific Anti-thrombmentioning
confidence: 99%
“…Passive mixing behavior typically relies on diversified microchannel structural design for fluid flow guiding along the wall and distortion to obtain the desired mixing performance . Hence, the improvement and optimization of the passive micromixer structure have always been the focus of research; a variety of passive micromixers with diverse structures have been implemented …”
Section: Introductionmentioning
confidence: 99%